BEYOND SUN, SAND, AND STITCHES: ASSIGNING RESPONSIBILITY FOR THE HARMS OF MEDICAL TOURISM. (12th March 2012) - SNYDER, JEREMY; CROOKS, VALORIE; JOHNSTON, RORY; KINGSBURY, PAUL
ABSTRACT Medical tourism (MT) can be conceptualized as the intentional pursuit of non‐emergency surgical interventions by patients outside their nation of residence. Despite increasing popular interest in MT, the ethical issues associated with the practice have thus far been under‐examined. MT has been associated with a range of both positive and negative effects for medical tourists' home and host countries, and for the medical tourists themselves. Absent from previous explorations of MT is a clear argument of how responsibility for the harms of this practice should be assigned. This paper addresses this gap by describing both backward looking liability and forward looking political responsibility for stakeholders in MT. We use a political responsibility model to develop a decision‐making process for individual medical tourists and conclude that more information on the effects of MT must be developed to help patients engage in ethical MT.